Victim of Sameblood Sexual Violence toward Children - Soetji Andari (Jurnal Penelitian Kesejahteraan Sosial, 2016)
Incest is one type of sexual disorders, the sameblood relationship for example brother and sister, father and daughter, mother and son, or uncle and nephew. Socially, sexual intercourses happen due to the rooms in the house thatdid not allow parents, children, or brothers and sisters living separately as socially functioning. The research was done through qualitative-descriptive method to determine people’s knowledge about sexual violence. It found that victims and perpetrators relations in Batam can be concluded that the forms of violences moslyt related to sexual violence. The act of sexual abusse manifested in sexual harassment, rape, and exploitation. Perpetrators are related by the biologically same blood, as father or stepfather, uncle, and grandfather. The violences mostly took place in the most privat space, homesmostly in the slums, and isolated areas.